Improvvisazione ed errore: a lezione da Miles (e Monk) - Bertinetto, Alessandro (Scenari, 2021)
In this paper I will take a cue from two statements attributed to Miles Davis to discuss an important aspect of what artistic improvisation teaches us about human practices: unexpected, perhaps unwanted, situations can be surprising stimuli to exercise our creativity, rather than remaining elements disturbing or just trivial errors. This exercise of creativity is the way we construct normative orders in our everyday and artistic practices.